Interactive simple notes for Sejarah in PT3 / Rajihah Razali - Razali, Rajihah (2016)
History or Sejarah in Malaysia serves subsidiary purpose instead of taught mere knowledge and love of the history. Initially, Sejarah had less attention given during the time of pre independence but it started focus on unity and integration of race after the Second World War and become the core subject starting from 1989. However, the popularity of Sejarah with reading and memorizing a lot of facts make it known as a boring subject. The excessive usages of textbook create the stereotypical lesson, less creativity and imaginative because of the nature of textbook that is static and not interactive. A mobile application of simple notes for Sejarah will be developed to help the students who take Pentaksiran Tingkatan 3 (PT3) exam in understanding and memorizing better towards this subject using pedagogical approach and scaffolding technique. This project will be developed in Malay language in order to help the students and this application communicate effectively. An ADDIE model will be used for a step-by-step guidance in developing this project. This approach can be improved with the help of the technological appliances such as the mobile device as students nowadays prefer to use smartphone in getting information instead of book form and it allows an anytime and anywhere access to the activities.